Traditional Chinese Customs in Thai Royal Court - Wongjongjaihan, Metta (Journal of Sinology (วารสารจีนวิทยา), 2017)
“Thailand and China are one family,” this remark is very familiar to Thai people. In fact, Thailand did establish the close ties with China since Sukhothai Kingdom (corresponding to Yuan Dynasty of China). The relationship is mostly in terms of trade and commerce. Since then, people of both lands have conducted business; thereby learning and exchanging the culture of each other. As a result, Thai people from the past to the present have known such Chinese festivals as Chinese New Year, Tomb-sweeping Day, Mid-Autumn Festival and Dragon Boat Festival well. Even the Thai Royal families also holds the ceremonies related to Chinese tradition like the Royal ceremony of offering food alms to monks during Chinese New Year Festival, the Royal homage to the ancestors’ spirits tablets, and the Chinese funeral Royal rituals.